З досвіду організації польових археологічних семінарів - Отрощенко, В.В.; Бровендер, Ю.М. (Археологія і давня історія України, 2010)
Стаття знайомить з досвідом проведення польових науково-практичних семінарів (ПНПС) на
місцях тривалих розкопок відомих пам’яток археології в межах Луганської області. Статья посвящена опыту организации полевых
научно-практических семинаров (ПНПС) на археологических раскопках в Луганской области. По
инициативе Центрально-Донецкой экспедиции и
Донбасского государственного технического университета (г. Алчевск), Института археологии НАН
Украины и Воронежского госуниверситета (Россия)
проведены 5 капитановских (1995—1999 гг.) и 9 картамышских ПНПС (2002—2010 гг.). Межгосударственный характер проекта обеспечил проведенным семинарам статус международных. Proposed paper discusses the experience of organization
of scientific and practical field seminars (SPFS)
conducted on the base of archaeological excavations
in Lugansk district. By the mutual initiative of Central-
Donetsk expedition, Donbass State Technical
university (Alchevsk city), Institute of archaeology of
NUAS, and Voronezh state university (Russia) five Kapitanovka
and nine Kartamysh SPFS were conducted between 1995—1999 and 2002—2010, respectively. Interstate
character of the project provides the international status to these seminars.